2020
DOI: 10.1007/s41030-020-00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Critically Ill Patients with COVID-19: A Narrative Review on Prone Position

Abstract: Introduction Prone position is known to improve mortality in patients with acute respiratory distress syndrome (ARDS). The impact of prone position in critically ill patients with coronavirus disease of 2019 (COVID-19) remains to be determined. In this review, we describe the mechanisms of action of prone position, systematically appraise the current experience of prone position in COVID-19 patients, and highlight unique considerations for prone position practices during this pandemic. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 52 publications
(142 reference statements)
0
30
0
2
Order By: Relevance
“…During the COVID-19 pandemic, the number of patients with moderate-to-severe ARDS has increased considerably and prone position has gained importance as an adjunctive treatment of severe hypoxemia ( Qadri et al, 2020 ). Prone position maneuver during mechanically ventilation is reported as safe and feasible, even though the incidence of several complications (including pressure ulcers) is higher for patients prone than those treated in supine position ( Girard et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the number of patients with moderate-to-severe ARDS has increased considerably and prone position has gained importance as an adjunctive treatment of severe hypoxemia ( Qadri et al, 2020 ). Prone position maneuver during mechanically ventilation is reported as safe and feasible, even though the incidence of several complications (including pressure ulcers) is higher for patients prone than those treated in supine position ( Girard et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“… 25 In a recently published study, it was reported that the prone position can temporarily improve hypoxemia but does not change the course of the disease and intubation rates in patients who are spontaneously breathing and not yet have been intubated. 26 In our cohort group, intermittent prone position was applied to two patients, two of whom were intubated and one of whom was spontaneously breathing with high-flow nasal cannula support. Although the sample size is not insufficient for evaluating the application of the prone position, our clinical experience indicate that the prone position does not decrease the need of intubation and mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Pronation maneuvers are an important element in managing patients undergoing mechanical ventilation for respiratory failure and Acute Respiratory Distress Syndrome (ARDS), in order to increase tissue oxygenation through an improvement in the ventilation/perfusion mismatch [ 6 , 7 ]. This maneuver requires a degree of physical effort, as well as the presence of multiple healthcare professionals for a correct execution of the technical gesture [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%